Study of SrEr0.04Fe1.96O4/PANI nano-composites for high-frequency applications. Issue 12 (15th June 2023) - Zeshan, Muhammad; Ali, Mahmood; Alanazi, Meznah M.; Abdelmohsen, ShaimaaA.M.; Khosa, Rabia Yasmin; Al-Sehemi, Abdullah G.; Ansari, Mohd Zahid; Tayeb, Roaa A.; Tahir Farid, Hafiz Muhammad; Rahman, Mohammed M.
Abstract: High-frequency nanocomposites have gained attention as electronic and telecommunication technologies. These nanocomposites consist of ferrite and a polyaniline matrix. Sol-gel technique was used to generate the ferrite nanomaterial, and in-situ synthesis was used to generate the polyaniline. The X-ray diffraction (XRD) analysis elucidated the existence of a single-phase structure comprising SrEr0.04 Fe1.96 O4 ferrite particles dispersed throughout the polyaniline matrix. To counteract the amorphous nature of polyaniline, adding spinel ferrite to nanocomposites boosted their crystallite size (20 nm–56 nm). When ferrite was combined with polyaniline, the dielectric constants and dielectric loss ( ε ′, ε ″ ) were found to decrease as a function of frequency. The ferromagnetic characteristics of the manufactured composites were discovered through hysteresis loop analysis. Saturation Ms, remanence Mr, and coercivity Hc all increased with ferrite content. Direct current (dc) resistivity and activation energies of the composite sample enhanced with concentration of polyaniline in ferrites. Improvements in all the properties of nanocomposites (FP4) may be suitable candidates for high frequency applications.